A Literature Review of the Knisley Learning Model in Mathematical Ability - Fitri Irawijayanti; Fatkurochman; Siti Afrianti; Iqbal Rosid (Review of Education, Science, and Technology, 2025)
Mathematics education requires innovative strategies that foster higher-order thinking skills while enhancing student engagement. The Knisley Learning Model (KLM), grounded in Kolb’s experiential learning theory, offers a student-centered approach through the stages of concrete experience, reflection, abstract conceptualization, and active application. This study aims to examine the effectiveness of KLM in improving students’ mathematical abilities, particularly in conceptual understanding, communication, creative thinking, and problem-solving. A literature review method was employed, analyzing relevant prior research findings. The analysis indicates that implementing KLM significantly enhances learning outcomes, strengthens motivation, and connects abstract concepts to real-life contexts. However, limitations include extended time requirements, group discussion dynamics that demand teacher facilitation skills, and dependency on adequate learning resources. The study implies the necessity of strengthening teachers’ pedagogical capacity through training, creativity in designing contextual materials, and utilizing digital technologies to support model implementation. Consequently, KLM has the potential to serve as a relevant and sustainable learning strategy, while opening opportunities for future research to develop innovative teaching materials and explore its integration with other instructional approaches.